2021
DOI: 10.3390/biology10101006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Spinal Cord Injury Model Permissive to Study the Cardiovascular Effects of Rehabilitation Approaches Designed to Induce Neuroplasticity

Abstract: As primary medical care for spinal cord injury (SCI) has improved over the last decades there are more individuals living with neurologically incomplete (vs. complete) cervical injuries. For these individuals, a number of promising therapies are being actively researched in pre-clinical settings that seek to strengthen the remaining spinal pathways with a view to improve motor function. To date, few, if any, of these interventions have been tested for their effectiveness to improve autonomic and cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…up to 4 h post‐injury), and level of injury (i.e. T2−3) are sufficient to cause a marked decrement in cardiac contractile function, evidenced by a significant reduction in E es in both rodent and porcine models (Fossey et al., 2022; Poormasjedi‐Meibod et al., 2019; Squair et al., 2018; Wainman et al., 2021; Williams et al., 2020). Moreover, in a recent manuscript, describing a series of experiments in both rodents and individuals with SCI, we reported that SCI induces considerable contractile dysfunction post‐injury that occurs due to the loss of bulbospinal sympathetic control over the heart (Fossey et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…up to 4 h post‐injury), and level of injury (i.e. T2−3) are sufficient to cause a marked decrement in cardiac contractile function, evidenced by a significant reduction in E es in both rodent and porcine models (Fossey et al., 2022; Poormasjedi‐Meibod et al., 2019; Squair et al., 2018; Wainman et al., 2021; Williams et al., 2020). Moreover, in a recent manuscript, describing a series of experiments in both rodents and individuals with SCI, we reported that SCI induces considerable contractile dysfunction post‐injury that occurs due to the loss of bulbospinal sympathetic control over the heart (Fossey et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were randomly assigned to either naïve or with injury to the spinal cord (severe contusion injury at the T3 spinal level). All procedures associated with inducing injury and pre‐ and post‐operative care have been described in detail previously (Wainman et al., 2021). Briefly, rats were initially anaesthetized using an inhalant anaesthetic (5% isoflurane chamber induction, and maintenance on 1.5−2% isoflurane, Piramal Critical Care, Bethlehem, PA, USA) and received enrofloxacin (10 mg/kg; Bayer Animal Health, Shawnee, KS, USA), buprenorphine (0.5 mg/kg; Ceva Animal Health, Cambridge, ON, Canada) and warmed lactated Ringer solution (5 ml subcutaneously; Baxter Corporation, Portland, OR, USA).…”
Section: Methodsmentioning
confidence: 99%